Comparison of scale and otolith age readings for trahira, Hoplias malabaricus (Bloch, 1794), from Paraná River, Argentina. (24th August 2013) - Lozano, I. E.; Llamazares Vegh, S.; Dománico, A. A.; Espinach Ros, A.
Summary The aim of this work was to compare age determinations and precision using two deposition structures of trahira Hoplias malabaricus (Bloch, 1794): the scales, which are most frequently used, and otoliths (lapilli). The length‐age relationships were obtained with both structures and compared with results from previous studies. The 163 sets of trahira otoliths (lapilli) and scales were 17–46 cm standard length (SL) from Cayastá (Santa Fe) and Islas Lechiguanas (Entre Ríos), Paraná River, Argentina. Three independent readings of each structure were conducted. An age bias plot was performed to compare age estimations from scales and otoliths. To assess the precision of age determinations using both structures, the percent agreement among readers for both structures and the coefficient of variation were calculated (%CV). The age‐length relationships were plotted and fitted with the von Bertalanffy growth function for both structures and compared with previous works. Age readings recorded for scales were lower than those recorded for otoliths for ages above or equal to 3 years. Percent agreement among readers was higher than 80% for otoliths and less than 65% for scales. The%CV obtained for scales was 20% for young fish and 17% for adults. For otoliths the %CV was 7% for young fish and 3% for adults. The %CV obtained for scales was over the recommended limit (>7.6%). The von Bertalanffy parameters for scales were Linf = 45.80 mm; k = 0.29; t0 = −1.34 and for otoliths were Linf = 40.76 mm; k = 0.39; t0 = −1.05. Precision of age estimations assessed from the percent agreement and the coefficient of variation indicates that the scales of the trahira are inappropriate to estimate age in population studies for juvenile and adult specimens.